An Efficient and Low‐Cost Photolithographic‐Pattern‐Transfer Technique to Fabricate Electrode Arrays for Micro‐/Nanoelectronics. Issue 1 (9th March 2016) - Li, Yongtao; Huang, Le; Zhong, Mianzeng; Wei, Zhongming; Li, Jingbo
Abstract : A novel and low‐cost technique for fabricating electrode arrays of micro‐/nanoelectronics is proposed. Such photolithographic pattern transfer is especially reliable for the 2D‐material‐based (opto)electronics such as transistors, top gate devices, Hall bars, heterostructure diodes, etc.